Intra-population Variability of Two Chrysichthys Species in six Aquatic Ecosystemes of Côte d’Ivoire - T.A.S. Coulibaly-Ouattara; A.B. Adepo-Gourene (European Scientific Journal, ESJ, 2023)
In Côte d'Ivoire, fish of the genus Chrysicthys colonise most hydrosystems. Setting up a sustainable management programme for these fish requires in-depth knowledge of the different species. The aim of this study was to assess the morphological variability of populations of two species of the genus Chrysichthys. To do this, forty-one morphological measurements were taken on 167 specimens of the species C. maurus and 160 specimens of the species C. nigrodigitatus. Discriminant factor analysis and hierarchical classification analysis were used to determine intra-specific variability. The differences between the populations indicate the probable existence of phenotypic plasticity linked to their environment. The similarities can be explained by a potential capacity for exchange of individuals between populations.